Improved off‐grid wind/photovoltaic/hybrid energy storage system based on new framework of Moth‐Flame optimization algorithm. (28th December 2021) - Abbassi, Abdelkader; Mehrez, Rached Ben; Abbassi, Rabeh; Saidi, Salem; Albdran, Saleh; Jemli, Mohamed
Summary: This paper suggests a new sizing optimization method of an off‐grid renewable energy system. To perform an accurate analysis of the distribution of the exchanged energy with all storage elements, the discrete Fourier transform tool has been used. Besides, different frequency strains have been achieved in accordance with the dynamic of each storage device. Thus, the problem formulation targets the minimization of the Total Cost of Electricity (TCE) for the purposes of improving the reliability, and increasing the performance and the exploitation of the renewable energies for electrification fulfillment. The Loss of Power Supply Probability (LPSP) is also considered to improve the reliability rate of the selected configuration. Considering all storage dynamics to achieve the energy management strategy, a modified Moth‐Flame Optimization (MFO) algorithm is proposed to address this problem. Based on economic evaluation and analysis, an optimal configuration of the system has been established. Referring to a high level of economic feasibility, the obtained results affirm that this architecture is able to deal successfully with the current sizing problem through its flexibility to achieve the lowest cost which is decreased by around 0.7 e 04 $ compared with the start of the search for the desired solution. Abstract : This paper proposes a new sizing optimization approach of an off‐grid renewable energy system. Based on modified Moth Flame Optimization (MFO) algorithm, a high level of economic feasibility in accordance with significant saved cost is achieved and demonstrated.